2009
DOI: 10.1007/s10722-009-9484-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and extent of diversity in Cucumis species in the Aravalli ranges of India

Abstract: Among the 52 species reported in Cucumis, cucumber and muskmelon are the most important species, extensively cultivated by the human for consumption. Diversity has been reported in the wild species of Cucumis from India. Considering the status of genetic erosion of the variability in the various species of Cucumis, a total of 121 germplasm accessions of five different Cucumis species were collected through three explorations in the parts of Aravalli ranges of northwestern India. The paper presents the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The Himalayan entities C. callosus and C. trigonus (names often synonymized with each other and/or with C. melo) (17,40,41) produce fertile F1 offspring when crossed with C. melo (34) and clearly are the wild progenitor from which melon was domesticated. The melon land races occurring in South and East Asia exhibit high genetic diversity (23)(24)(25)(26)42) and deserve to be sampled more densely in future studies. The surprising finding that an Australian species (C. picrocarpus) is the sister of the C. melo/C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Himalayan entities C. callosus and C. trigonus (names often synonymized with each other and/or with C. melo) (17,40,41) produce fertile F1 offspring when crossed with C. melo (34) and clearly are the wild progenitor from which melon was domesticated. The melon land races occurring in South and East Asia exhibit high genetic diversity (23)(24)(25)(26)42) and deserve to be sampled more densely in future studies. The surprising finding that an Australian species (C. picrocarpus) is the sister of the C. melo/C.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the impressive species richness in Africa and the identical chromosome number of C. melo and African Cucumis, modern authors have held that C. melo is of African origin (18)(19)(20)(21)(22). This view has persisted even in the face of genetic data pointing to greatest genetic diversity in Indian and East Asian landraces of C. melo (23)(24)(25)(26) and despite numerous failed attempts to produce fertile F1 offspring from crosses of C. melo and African species of Cucumis (17).…”
mentioning
confidence: 99%
“…Bitter fruits and leaves of wild cucurbit plants have been used as a purgative and emetic in India (6). The bitter fruit stem of melon (in Chinese, "gua di") is prescribed as a traditional hepatoprotective medicine whose effect and usage were well documented in Ben Cao Gang Mu, the Chinese Encyclopedia of Botany and Medicines composed by the Ming Dynasty physician Li Shi-Zhen in 1590 CE.…”
mentioning
confidence: 99%
“…It is a genus of more than 52 species, indigenous mainly to tropical Africa, also Asia, Australia and some islands in the Pacific. A lot of works that have been done by the researchers throughout the world on various plants of this family indicated a number of cucurbitacins (triterpens like compounds) were isolated from genus Cucumis [16,17].…”
Section: The Genus Cucumismentioning
confidence: 99%
“…Results obtained in the survey conducted by different researchers indicated that Cucumis were used by the people of various regions and tribes in the world. The diseases for which these plants were used includes bed wetting in children, bleeding from external cuts and wounds, burns, cancer, cholera, diabetes, ear disorders, eye disorders, fever, stomach ache, gastro-intestinal, goiter, heart disorders, hepatic disorders, infections, infertility, inflammation, malaria, menstrual disorders, mumps, paralysis, pox, respiratory tract disorders, skin disorders, sexual disorders, sexually transmitted diseases, sun stroke, tetanus, tuberculosis, typhoid, and vomiting [17]. According to reported by researchers, the whole plant parts of Bitter gourd or bitter melon Cucurbitaceae family are used in the treatment of malaria in the south-western regions of Nigeria.…”
Section: Use In Ethnomedicinementioning
confidence: 99%